Aminosalicylic Acid Inhibits IκB Kinase α Phosphorylation of IκBα in Mouse Intestinal Epithelial Cells - Yan, Fang (1999)
Tumor necrosis factor α (TNFα)-stimulated nuclear factor (NF) κB activation plays a key role in the pathogenesis of inflammatory bowel disease (IBD). Phosphorylation of NFκB inhibitory protein (IκB) leading to its degradation and NFκB activation, is regulated by the multimeric IκB kinase complex, including IKKα and IKKβ. We recently reported that 5-aminosalicylic acid (5-ASA) inhibits TNFα-regulated IκB degradation and NFκB activation. To determine the mechanism of 5-ASA inhibition of IκB degradation, we studied young adult mouse colon (YAMC) cells by immunodetection and in vitro kinase assays. We show 5-ASA inhibits TNFα-stimulated phosphorylation of IκBα in intact YAMC cells. Phosphorylation of a glutathione S-transferase-IκBα fusion protein by cellular extracts or immunoprecipitated IKKα isolated from cells treated with TNFα is inhibited by 5-ASA. Recombinant IKKα and IKKβ autophosphorylation and their phosphorylation of glutathione S-transferase-IκBα are inhibited by 5-ASA. However, IKKα serine phosphorylation by its upstream kinase in either intact cells or cellular extracts is not blocked by 5-ASA. Surprisingly, immunodepletion of cellular extracts suggests IKKα is predominantly responsible for IκBα phosphorylation in intestinal epithelial cells. In summary, 5-ASA inhibits TNFα-stimulated IKKα kinase activity toward IκBα in intestinal epithelial cells. These findings suggest a novel role for 5-ASA in the management of IBD by disrupting TNFα activation of NFκB.